Ophiopogonin A Alleviates Hemorrhagic Shock-Induced Renal Injury via Induction of Nrf2 Expression - Sheng, Xiaoming; Yang, Yang; Liu, JiaJia; Yu, Junbo; Guo, Qingsong; Guan, Wei; Liu, Fan (Frontiers in Physiology, 2021)
Ophiopogonin, including Ophiopogonin A, B, C, D, is an effective active component of traditional Chinese medicine Ophiopogon japonicus which has a wide range of pharmacological effects such as protecting myocardial ischemia, resisting myocardial infarction, immune regulation, lowering blood glucose, and anti-tumor. However, the functions of ophiopogonin A on hemorrhagic shock (HS)-induced renal injury remain unclear. Firstly, we construct the HS rat model and hypoxia HK-2 cell model to assess the effects of ophiopogonin A in vivo and in vitro. In vivo, HE and TUNEL staining show that ophiopogonin A dose-dependently inhibits HS-induced tissue damage and apoptosis. Moreover, ophiopogonin A dose-dependently downregulates the levels of blood urea nitrogen (BUN), creatinine (Cr), KIM-1, NGAL, iNOS, TNF-α, IL-1β, and IL-6 in HS rats kidney tissues, and decreases the number of MPO-positive cells. In vitro, we get similar results that ophiopogonin A dose-dependently improves hypoxia-induced HK-2 cell apoptosis and damage. In addition, ophiopogonin A dose-dependently increases the expression of Nrf2, while knockdown of Nrf2 reverses the functions of ophiopogonin A in vivo and in vitro. Furthermore, ophiopogonin A dose-dependently promotes the phosphorylation of ERK in HS kidney tissues and hypoxia-treated HK-2 cells, suggesting that ophiopogonin A functions via p-ERK/ERK signaling pathway.